THE QUALITY OF QUAIL EGGS AGED 12-16 WEEKS GIVEN FERMENTED DRAGON FRUIT PEEL JUICE THROUGH DRINKING WATER - I. W., Armanto; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika, 2024)
The study was conducted to determine the quality of quail eggs (Coturnix coturnix japonica) given fermented dragon fruit peel juice through drinking water at the age of 12-16 weeks. This research design used a Complete Randomized Design with three treatments and six replications. Each replication used 10 quails, bringing the total number of quails used is 180. 606 The treatment used was quail given drinking without fermented dragon fruit peel juice (P1) as a control, giving fermented dragon fruit peel juice in drinking water with a level of 4% (P2) and giving fermented dragon fruit peel juice in drinking water with a level of 6% (P3). The variables observed are: egg shape index, egg weight, haugh unit (HU), eggshell persentage, and yolk color. The results of this study showed that egg shape index, egg weight, haugh unit (HU), eggshell persentage, and egg yolk color were not statistically significantly increased (P>0.05). The result of the study is that fermented dragon fruit peel juice given to quail aged 12-16 weeks through drinking water has not been able to improve the quality of quail eggs.